2013
DOI: 10.1155/2013/547171
|View full text |Cite
|
Sign up to set email alerts
|

Breast Mass and Lytic Bone Lesions: A Rare Presentation of Non-Hodgkin’s Lymphoma Arising in the Breast

Abstract: Background. Primary breast lymphoma is a rare malignancy representing less than 1% of all tumors presenting in the breast. Case Presentation. A 55-year-old woman presented with altered mental status due to severe hypercalcemia and was found to have a large breast mass with lytic bone lesions in the calvarium of the skull. Biopsy of the mass revealed diffuse large B-cell lymphoma. Staging workup did not reveal any visceral organ or distant lymph node involvement. The patient's bone marrow biopsy was positive fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Patients suffer from acute, rapidly worsening pain which doesn't relieve with rest. Pathological fractures in this area results in impaired mobility, dysfunction and decreased quality of life [14].…”
Section: Discussionmentioning
confidence: 99%
“…Patients suffer from acute, rapidly worsening pain which doesn't relieve with rest. Pathological fractures in this area results in impaired mobility, dysfunction and decreased quality of life [14].…”
Section: Discussionmentioning
confidence: 99%
“…CRAB like initial presentation mimicking active myeloma is uncommonly reported in the literature. [3][4][5][6][7][8][9][10][11][12][13][14][15][16] In this manuscript we describe a middle-aged female subject who presented with clinicoradiological and biochemical features secondary to metastatic breast cancer mimicking CRAB positive myeloma and present a comprehensive review of all such CRAB positive nonmyelomatous malignancies reported in the literature.…”
Section: Crab (Hypercalcemia [C] Renal Dysfunction [R] Anemia [A] Bon...mentioning
confidence: 99%
“…There were twenty-two cases of CRAB positive nonmyelomatous malignancies (M:F = 1:1) the details of which are briefly summarized in Table 1. [3][4][5][6][7][8][9][10][11][12][13][14][15][16] The median age at presentation was 58. G reversal was described in a case reported by Roy et al in a case of primary osseous Burkitt lymphoma.…”
Section: Crab (Hypercalcemia [C] Renal Dysfunction [R] Anemia [A] Bon...mentioning
confidence: 99%
See 1 more Smart Citation